Compact Hexagonal Liquid Core PCF Package Using a Hollow Optical Fiber - Hwang, Jihyun; Park, Jiyoung; Baresari, Tavakol Nazari; Han, Seung-Ryong; Jhon, Young Min; Oh, Kyunghwan (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2018)
We proposed and demonstrated a novel method to package liquid-core hexagonal photonic crystal fibers (PCFs) by utilizing a hollow optical fiber (HOF) not only as a liquid delivery tube but also as a light launching pedestal. Compact all-fiber packaging with single mode fiber input and output was experimentally achieved. Various configurations of liquid core PCFs were demonstrated by controlling the inner diameter of HOF and offsets. Based on numerical analyses and light launching experiments, we confirmed that this method could substantially enhance the light-liquid interaction efficiency, structurally prevent liquid evaporation within PCF, and providing a new versatile liquid core PCF device platform.
Keywords: PHOTONIC CRYSTAL FIBERS; SINGLE-MODE FIBERS; REFRACTIVE-INDEX; FABRICATION; DEVICES